Dissemination and Implementation Science to Advance Health Equity: An Imperative for Systemic Change - Mcloughlin, Gabriella Maria; Martinez, Omar (CommonHealth, 2022)
Innovations in public health research and evidence-based interventions targeting chronic and infectious diseases are only effective if they reach their target populations. Individuals from low socioeconomic background, racial and ethnic minorities, and sexual/gender minority communities are most susceptible to chronic diseases such as obesity and cancer, and infectious diseases such as HIV and COVID-19. These disparities are driven by social and structural conditions including stigma and discrimination, housing instability and food insecurity. Accordingly, interventions that aim to improve population health must be targeted toward marginalized communities who are often systematically excluded from decision making processes. This article introduces dissemination and implementation science as a key opportunity to advance health equity through integrating measures and metrics that evaluate if an intervention is successful at improving health outcomes in marginalized populations. Implementation science also provides frameworks to help evaluate the key determinants to implementation success which can inform subsequent health outcomes. Examples of how researchers have engaged with community stakeholders are provided, along with ways in which dissemination has gone beyond traditional practices. Finally, ways in which universities can build capacity for implementation science as a means to address health disparities are provided with the goal of improving the translation of research to practice.